Advanced HIV as a Neglected Disease - Joe Jarvis (International Journal of Infectious Diseases)
Although HIV treatment coverage has increased substantially in recent years, the associated reductions in AIDS-related deaths have been smaller and slower than expected. The proportion of people with advanced HIV disease remains high: it is estimated that more than 4 million people have advanced HIV disease, and each year more than 600,000 of them are expected to die. Many of these deaths can be prevented. Until recently, advanced HIV was viewed as a problem of late presentation, so the solution was thought to be testing more people and diagnosing the disease earlier. Although late presentation remains problematic, however, advanced HIV is now predominantly seen among people who started care but were not effectively engaged or have disengaged, returning only when they're ill. This talk will discuss who is at risk for the worst outcomes; which infections lead to the greatest morbidity and mortality; new tools for diagnosing, preventing, and treating these conditions; and how systems could adapt to delivering these tools effectively.